ANALYZING KEY FACTORS INFLUENCING SHARE LIQUIDITY IN UZBEKISTAN - Kenjebaeva Gulfuza Rakhmatillaevna (Scholar Express Journals, 2024)
This article examines the significance of stock liquidity within Uzbekistan's stock market. Liquidity is crucial for successful investments, as it affects the ease with which shares can be sold at market price. The study analyses various factors that influence share liquidity, including trading volume, bid-ask spread, company financial stability, index inclusion, and market participant behaviour. Enhancing the stock market's liquidity and increasing liquid assets can improve the country's economic landscape, fostering new investment opportunities and corporate growth, and ultimately contributing to overall economic development.
Keywords: Share; liquidity; spread